Thermal analysis of water- ethylene glycol based chemically reactive ternary nanofluid flow with heat source and radiation - B. T. Raju; B. Chiranjeevi; Najiyah Safwa Khashi’ie; Vediyappan Govindan; Busayamas Pimpunchat (Journal of Radiation Research and Applied Sciences, 2025)
This study investigates the thermal behavior of a water–ethylene glycol based chemically reactive ternary nanofluid flow over a moving porous inclined plate under the influence of thermal radiation, temperature-gradient-dependent heat source, and an aligned magnetic field. The ternary nanofluid consists of SiO 2 , TiO 2 , and Al 2 O 3 nanoparticles dispersed in an ethylene glycol–water mixture to achieve superior thermal properties. The governing nonlinear partial differential equations for momentum, energy, and species concentration are formulated considering chemical reaction, internal heat generation, and magnetohydrodynamic effects, and are solved analytically using the Laplace transform technique. Important performance parameters such as Nusselt number, Sherwood number, and skin friction coefficient are evaluated and visualized through MATLAB-generated tables and graphs. The analysis reveals that nanoparticle addition reduces the Nusselt number by 1.54 %–6.39 %, indicating a decline in thermal performance, while higher thermal and solutal Grashof numbers enhance buoyancy forces, thereby increasing velocity near the heated surface. Increasing magnetic field strength, plate inclination, and porous resistance leads to significant velocity suppression, whereas thermal radiation and heat source parameters raise the temperature distribution considerably. To optimize the effects of governing parameters, Response Surface Methodology (RSM) is implemented, and ANOVA validation confirms the model accuracy with R 2 > 96 %.
Keywords: Nanofluid Flow and Heat Transfer; Heat Transfer Mechanisms; Heat transfer and supercritical fluids